Estimation of the power absorbed by the surface of optical components processed by an inductively coupled plasma torch - Jourdain, Renaud; Castelli, Marco; Yu, Nan; Gourma, Mustapha; Shore, Paul (Elsevier, 2016)
The focus of this work is the determination of the heat flux function -thermal footprint- of a plasma jet generated by an inductively coupled plasma (ICP) torch. The parameters of the heat flux function were determined through the correlation of modelling and experimental results. One surface of substrates was exposed to an impinging jet while the temperature changes of the unexposed surface was recorded, analysed and used to derive the parameters of the heat flux function. From a modelling viewpoint, a series of finite element analyses (FEA) were carried out to predict temperatures of substrate surfaces. From an experimental viewpoint, the plasma torch was powered by a 1 kW radio frequency signal generator tuned at 39 MHz. The ICP torch equipped with a De-Laval nozzle impinged the surfaces of selected substrates at atmospheric pressure. Three sets of experiments -static, single pass and multi passes- were carried out to determine and validate the numerical description of the plasma jet. Also this work enabled to determine the maximum intensity of the heat flux distribution and the total power absorbed by substrate surfaces. Finally, the most advanced numerical model was used to assess the effect of a bi-directional raster scanning strategy that was used for the processing of large optical components.
Keywords: Impinging jet; Local heat transfer; Moving plate; Nozzle plate